Association between consultations with complementary/alternative medicine practitioners and menopause-related symptoms: a cross-sectional study. (August 2015) - Peng, W.; Adams, J.; Hickman, L.; Sibbritt, D. W.
Abstract Objectives To examine the associations between consultations with complementary and alternative medicine (CAM) practitioners and menopause-related symptoms. Methods A cross-sectional survey of a nationally representative sample of 10 011 women aged 59–64 years from the Australian Longitudinal Study on Women's Health, conducted in 2010. Women, including those with hysterectomy, oophorectomy and natural menopause, were asked about their consultations with a range of CAM practitioners and menopause-related symptoms experienced. Results Acupuncturists were more likely to be consulted by women with hysterectomy experiencing night sweats (odds ratio, OR = 2.21), but were less likely to be consulted by those experiencing hot flushes (OR = 0.53). Acupuncturists were also more likely to be consulted by women with oophorectomy (OR = 3.11) and natural menopausal women (OR = 1.57) experiencing back pain. Massage therapists were more likely to be consulted by women with oophorectomy experiencing back pain (OR = 1.98), women with hysterectomy experiencing anxiety (OR = 1.52), and natural menopausal women experiencing back pain (OR = 1.54) and/or anxiety (OR = 1.29). Naturopaths/herbalists were more likely to be consulted by women with oophorectomy experiencing leaking urine (OR = 2.08). Chiropractors/osteopaths were more likely to be consulted by women across all menopausal status experiencing back pain (OR = 2.52, 2.31 and 2.25 for women with oophorectomy, hysterectomy and natural menopause, respectively). Conclusions There are substantial levels of CAM practitioners' consultations amongst menopausal women, with a range of menopause-related symptoms associated with the use of specific CAM practitioner modalities. It is important that health-care providers are mindful of CAM practitioner use in order to ensure safe, effective and coordinated treatment and support for menopausal women in their care.